Mussel-Inspired Hydrogels Incorporating Graphite Derivatives for Soft Tissue Regeneration - Filipa Fernandes; Daniela Peixoto; Cátia Correia; Magda Silva; Maria C. Paiva; Natália M. Alves (Nanomaterials)
Hyaluronic acid (HA)-based hydrogels offer a promising approach for soft tissue application due to their biocompatibility, tunable mechanical properties, ability to mimic the extracellular matrix, and capacity to support cell adhesion and proliferation. In this work, bioadhesive composite hydrogels were developed by integrating graphite derivatives (EG) into a dopamine-modified HA matrix (HA-Cat), which enhances tissue adhesion through catechol groups that mimic mussel-inspired adhesion mechanisms. The EG was functionalized via 1,3-dipolar cycloaddition reaction (f-EG), that allowed the anchoring of silver nanoparticles (f-EG-Ag) and grafting of hydrocaffeic acid (f-EG-Cat) on the functionalized EG surfaces. The hydrogels were produced by oxidative crosslinking of HA-Cat under mild basic pH conditions using sodium periodate. Indirect in vitro assays using L929 fibroblast cells showed high biocompatibility and enhanced cell proliferation at optimized composite hydrogel concentrations. These findings suggest that composite hydrogels could find an application as bioactive, adhesive scaffolds for the regeneration of soft tissues, where they can facilitate localized agent delivery and integration with the host tissue.